Internal Conflict and Governance
XX, 300 p.
Keywords: Violence, war and internal conflicts have assumed a new intensity with the decline of the Cold War. There are over 32 civil wars going on today. Our world may well witness over 100 million refugees in the year 2000 as a direct result of internal wars. This volume consists of case studies and theory-oriented papers dealing with Asia, Africa and Latin America and the Middle East. Taken together, they spell out implications of wide general interest, providing a comparative basis for a systematic approach to conflict transformation.